2015
DOI: 10.1007/s13277-015-4612-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in relation to TP53 codon 72 and CDH1 gene polymorphisms in the Bangladeshi women

Abstract: Pharmacogenomic studies play a significant role in understanding the risk of breast cancer where genetic abnormalities are implicated as the etiology of cancer. Various polymorphisms of tumor suppressor gene TP53 and E-cadherin (CDH1) have been found to be associated with increased breast cancer risk worldwide. This study aimed to analyze the contribution of TP53 and CDH1 gene anomalies in breast cancer risk in the Bangladeshi breast cancer patients. For risk determination, 310 patients with breast cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…To maintain the stability of the meta-analysis after the non-inclusion of deviant studies of HWE and sensitivity analysis, we evaluated the influence of each study on pooled OR. After the exclusion of studies [39][40][41][42], no study has shown a significant influence of the pooled OR effect in each of the different genetic models ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To maintain the stability of the meta-analysis after the non-inclusion of deviant studies of HWE and sensitivity analysis, we evaluated the influence of each study on pooled OR. After the exclusion of studies [39][40][41][42], no study has shown a significant influence of the pooled OR effect in each of the different genetic models ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, none of the studied SNPs showed any significant correlations with patients’ epidemiological or tumor or histological features. Shabnaz et al also did not find any correlation between − 160C/A polymorphisms with clinicopathological characteristics of BC patients [18]. However, Tipirisetti et al noted a positive correlation between the − 160A allele occurrences in patients with advanced stage [19].…”
Section: Discussionmentioning
confidence: 99%
“…Sarrió et al [36] 2003 Spain 45/20 N.S. Cattaneo et al [42] 2006 Central Italy (Lazio) 99/246 N.S. Yu et al [39] 2006 Taiwan 468/470 Minor allele carriers (rs16260 A) were 30% more likely to be breast cancer cases than women with only the major allele (C).…”
Section: Discussionmentioning
confidence: 99%
“…Cattaneo et al [42] investigated a sample of the Italian population and found no association between the -160 C/A SNP and breast cancer risk (OR = 1.35, 95 % CI = 0.84-2.17). Lei et al [37] found the same result among the Swedish as well as Czech populations.…”
Section: The Role Of E-cadherin Polymorphisms In Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation